Examining the Influence of Principal Leadership on School Effectiveness : A Comprehensive Analysis in The Context of Primary Schools in Surabaya - Windasari, Windasari; Trihantoyo, Syunu; Roesminingsih, Erny; Vasodavan, Vinotini (Jurnal Paedagogy, 2024)
This study aims to analyze the influence of principal leadership on the effectiveness of primary schools. This research used a quantitative method. The research targets teachers in Surabaya, utilizing a sample of 376 respondents selected through a systematic random cluster sampling technique. The research instrument Principal Leadership adapted "The Successful School Leadership Survey," comprising 22 items, and the school effectiveness instrument was adapted "PESOC," consisting of 17 items from previous studies. Data was collected using an online questionnaire administered through Google Forms. The analysis employed Structural Equation Modeling with Partial Least Squares (SEM PLS), encompassing both inner and outer model evaluations. The study's result was that principal leadership positively affected the effectiveness of schools. The research findings strongly supported the notion that the leadership exhibited by school principals was a critical factor in the establishment and maintenance of effective schools. The study emphasized the importance of leadership that specifically addresses the four dimensions outlined in the Successful School Leadership survey, highlighting their integral role in shaping and sustaining educational institutions that are deemed effective.